TIDAL DYNAMICS STUDY OF MOROWALI WATERS USING NUMERICAL MODEL DELFT3D - Azhiz, Putra
Morowali waters have numerous potentials and unique characteristics, such as: seaweed cultivation area, meeting point of three tectonic plates, and fisheries catchment area. Furthermore, Morowali has been known for its nickel resources and thus the area is being developed as potential nickel mines. Despite the potentials of the area, there isn’t sufficient related research about the hydrodynamics of the area. This research focuses on the hydrodynamic characteristics of Morowali waters, spesifically tides and tidal currents. This research is conducted using hydrodynamic model DELFT3D. The simulation is done using only tides as the generating force. The required datas are acquired from Tide Model Driver (TMD) for tides, Global Bathymetry Chart of the Oceans (GEBCO) for bathymetry, and field study of tides and topographical characteristics. Harmonic analysis is utilized to determine the tidal type and current circulations are plotted spatially. The simulation returns an RMSE of 0.06 m, percent error of 8,32 %, and Aida number ???????? 1.03 and ???????? 1,27. Referring to the Formzahl number of 0.87, it can be determined that the tidal type of the area is mixed prevailing semidiurnal. The dominant constituent is found to be M2 with an amplitude of 0,45 – 0,6. Maximum average velocity of the current reaches 0,021 m/s, flowing from north to south from low water en route to high water and high water itself and reversing in direction from south to north on high water en route to low water and low water condition, taking into account the forcing used in the model is resctricted to only tides. The residual current velocity is bigger than that of tidal currents for the observation data, so it can be concluded that Morowali waters are dominated by residual current.